2020
DOI: 10.1111/cdev.13389
|View full text |Cite
|
Sign up to set email alerts
|

Infant and Toddler Child‐Care Quality and Stability in Relation to Proximal and Distal Academic and Social Outcomes

Abstract: This study considered the quality and stability of infant and toddler nonparental child care from 6 to 36 months in relation to language, social, and academic skills measured proximally at 36 months and distally at kindergarten. Quality was measured separately as caregiver-child verbal interactions and caregiver sensitivity, and stability was measured as having fewer sequential childcare caregivers. This longitudinal examination involved a subsample (N = 1,055) from the Family Life Project, a representative sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…When children approach preschool age, social skills and language become more reciprocal and integrated; more socially competent children engage in more language exchange opportunities while children who have received limited language input at home from caregivers will engage in fewer social interactions, thereby experiencing fewer opportunities to improve social competence ( 1 , 39 ). For instance, Bratsch-Hines et al ( 40 ) evaluated this pathway longitudinally: more positive parent-child verbal interactions contributed to stronger language skills at child age 3 years as well as stronger child social skills in kindergarten. While Barnett et al ( 1 ) identified similar associations between sensitive, positive parenting, language gains, and social competence gains during toddlerhood, most work to date has focused on growth in either language ( 41 , 42 ) or social competence ( 43 , 44 ), not both child development outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…When children approach preschool age, social skills and language become more reciprocal and integrated; more socially competent children engage in more language exchange opportunities while children who have received limited language input at home from caregivers will engage in fewer social interactions, thereby experiencing fewer opportunities to improve social competence ( 1 , 39 ). For instance, Bratsch-Hines et al ( 40 ) evaluated this pathway longitudinally: more positive parent-child verbal interactions contributed to stronger language skills at child age 3 years as well as stronger child social skills in kindergarten. While Barnett et al ( 1 ) identified similar associations between sensitive, positive parenting, language gains, and social competence gains during toddlerhood, most work to date has focused on growth in either language ( 41 , 42 ) or social competence ( 43 , 44 ), not both child development outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, it is expected that measures of individual differences in ToM should exhibit similar strength associations with measures of social competence. Given that both social competence and ToM have been linked with individual differences in verbal ability, socioeconomic status, gender, and a range of developmental conditions (e.g., Bratsch-Hines et al, 2020; Weimer et al, 2021), it is also important to consider the impact of these confounds when attempting to establish unique associations between ToM and children’s social competence. Supporting the validity of the Strange Stories and Silent Film tasks, scores on these tests are moderately associated with teachers’ ratings of children’s social competence at school (Devine & Apperly, 2022), even when confounding variables such as language and socioeconomic status are considered.…”
Section: Measuring “Advanced” Tommentioning
confidence: 99%
“…The type of facility, the qualification system, as well as the frequency of the ECEC experience among Japanese children varies from the experience of children living in other countries. In the US, infants and children up to 24 months experienced ECEC for approximately 24 hours and 32 hours per week, respectively [23,24]. Generally, facility-based childcare does not have sufficient opening hours to accommodate the working hours of parents.…”
Section: Evidence Requirements For the Effectiveness Of The Quality O...mentioning
confidence: 99%